De netelige kwestie van het aantal bedrijfswagens in België - Xavier May (Brussels Studies)
Many different figures are mentioned regarding the number of company cars in Belgium. A definition is adopted and two types of beneficiary are identified. However, the analysis of official statistics shows that no source allows us to determine the number of company cars in Belgium, although it is certain that their numbers have increased rapidly over the past decade. An attempt to quantify the number of vehicles concerned is carried out as well as a mapping of the places of residence of beneficiaries for all districts...